Lifetime alcohol intake and pattern of alcohol consumption in patients with alcohol-induced pancreatitis in comparison with patients with alcohol use disorder. (3rd June 2018) - Juliusson, Sigurdur Jon; Nielsen, Jon Kristinn; Runarsdottir, Valgerdur; Hansdottir, Ingunn; Sigurdardottir, Ragna; Björnsson, Einar S.
Abstract: Objective: To examine lifetime drinking patterns in men and women with alcohol-induced pancreatitis (AIP) in comparison with patients with alcoholic use disorder (AUD) without pancreatic disease. Methods: Alcohol consumption patterns were assessed using a validated questionnaire, the Lifetime Drinking History (LDH), during an outpatient visit. Patients diagnosed with AIP were matched for gender and age (+/− 5 years) with patients with AUD in addiction treatment. Results: A total of 45 patients with AIP (35 males, 10 females) and 45 AUD patients were included. Alcohol consumption patterns were not significantly different between males and females with AIP and those with history of acute AIP and chronic pancreatitis (CP). Alcohol consumption patterns of AIP and AUD patients were similar in terms of onset age and duration of alcohol consumption, lifetime alcohol intake and drinks per drinking day. A higher proportion of binge drinking was found among patients with AUD than those with AIP (median 1.00 vs. 0.94, p  = .01). Males with AUD had lower onset age (15 vs. 16 years, p  = .03), higher total amount of spirits (35520 vs. 10450 drinks, p  = .04) and higher proportion of binge drinking (1.00 vs. 0.97, p  = .01) than males with AIP, whereas females with AIP and AUD had similar drinking patterns. Conclusions: Alcohol drinking patterns and lifetime drinking history was similar in patients with AIP and patients with AUD. Males with AIP had lower total amount of spirits and lower proportion of binge drinking than those with AUD, suggesting the idiosyncratic etiology of AIP.